Early mobilization in ICU patients: a review study (Research, Society and Development, 2023)
Introduction: The patient usually stays in the ICU for a considerable period of time, causing a malfunction in musculoskeletal functions. Faced with such complications, physiotherapy through early mobilization reduces the length of hospital stay, as well as seeks to prevent possible musculoskeletal disorders of the patient in the ICU. Objective: To analyze the benefits of early mobilization in ICU patients. Methodology: This is an integrative literature review, based on publications in journals indexed in the Scientific Electronic Library Online (SciELO), Google Scholar, and Medical Publications (PubMed) databases. Conclusion: The results of the studies proved that, the less time the patient stays in bed, the better it will be for his functional health, and in this context, the physiotherapeutic exercises of early mobilization are of fundamental importance, since they prevent functional kinetic dysfunctions of the patient.